Teorias da saúde e fenomenologia da enfermidade - Gründling, Alexandre de Ugalde (2021)
The main purpose of this work is to provide a phenomenological approach to illness. It examines three phenomenological approaches to the experience of the disease. First, It presents the main health theories, namely: the hypocritical theory, the biostatistics, and the holistic theory (in which the phenomenological approach is situated). According to the Hippocratic conception, health consists of a balance and equilibrium between bodily moods, which are qualities of a particular elementary constitution of the individual; in turn, the biostatistics theory considers health as the absence of disease. In this case, It makes a statistical analysis of an empirical ideal of the population to establish a normality pattern through which any deviation is taken as a disease; holistic theory aims to provide a global perspective on the person, considering health as the ability to act in standard circumstances. In this case, the objective fulfillment and circumstances are established in a normative way, concerning well-being and minimal happiness as criteria. The phenomenology of illness, although situated within the holistic health theories field, specifically directed to first-person experience of the disease. In this sense, this work reconstructs the experience concept from three phenomenological approaches. The first, named the paradigm of the lived body, privileges the corporeal aspects and presents a phenomenological conception about the essential structures of the lived body; the second one presents a perspective of hermeneutic phenomenology, in which the existential aspects of finding oneself (Befindlichkeit) - thrown into the world - and the attunement (Stimmung), take the foreground in describing the structure of illness experience; the third approach, in turn, presents a conception of experience whose phenomenological core revolves around the feeling of bodily certainty. This feeling is characterized by being basic and basic, guaranteeing a sense of reality and familiarity with the world. Finally, the experience of illness is thematized by phenomenological reconstructed approaches. In the case of the paradigm of the lived body, illness is described as an experience of the body presenting itself as an uncanny and as an alien presence, but also in its dysfunctional appearance (dys-appearance). This experience is also described in terms of a series of losses such as totality, control, and so on. In the hermeneutic phenomenology approach, the illness emerges as the experience of the world as hostile and unhomelikeness, revealing the uncanny attunement. The last approach presents the experience of illness as bodily doubt, which reveals several changes elucidated in terms of a loss of experiential continuity, bodily transparency, and bodily belief. Among the results obtained, the central element promoted by the analysis and description of the experience of illness to health sciences stands out. In this case, the central role of phenomenology is also highlighted, as it makes possible a theoretical contribution for qualitative investigations about illness experience. The work also shows that illness can provide a privileged perspective, both for philosophy and for the investigation of experience, insofar as it shows up tacit background structures.